Badanie zmienności kosztów przedsiębiorstwa handlu detalicznego w warunkach współliniowości zmiennych kosztotwórczych - Witkowski, Marek (Digitalizacja i deponowanie archiwalnych zeszytów RPEiS sfinansowane przez MNiSW w ramach realizacji umowy nr 541/P-DUN/2016, 1990)
The article undertakes an attempt to investigate the variability of cost of a retail enterprise. The problems connected with this task are not easy to solve. They require the methods that would reduce negative consequences of strong corelations between variables explaining the variability of costs. The existence of such corelations (i.e. of co-linearity of variables) is detrimental for a correct determination of intensity and direction of influence of particular cost-creating factors on cosi It may also be responsible for mistaking an insignificant cost- -creating variable for a significant one. Nowadays, many methods of neutralizing co-linearity exist. Among them, ridge regression method is considered highly efficient. The article exemplifies application of the latter method to the cost analysis of a retail enterprise and compares its results with the results of the classic method of smallest squares by verifying the regression models of cost assessed by both methods. The advantages and disadvantages of ridge regression method in the context of classic regression method have been examined.
The analysis of variability of cost of a retail enterprise in conditions of co-linearity of cost-creating variables